Analisis Framing Pemberitaan Isu Rasisme Kematian George Floyd di CNNIndonesia.com Periode 28 Mei–29 Juni 2020 - Tititri Ari Kurnia; Rama Kertamukti (School of Communication Science and Media Business, 2022)
The mass media helps the community with one of its information demands. Information can be accessed by the public through mass communication channels like print, electronic, and online media. People from different nations can access information at a location that is hard to go to fast and easily using online media. similar to one of the circumstances of George Floyd's passing on May 25, 2020 in Minneapolis, United States. George Floyd is a very hot issue in a variety of internet media, including social media, because of how quickly and easily one may access online media. The purpose of this study is to ascertain how the online news source CNN Indonesia.com presents the story about the racism controversy surrounding the American death of George Floyd (28 May-29 June 2020). The theory of Media Reality Construction and Reporting is applied in this study. Purposive sampling was employed in this study along with Robert N. Entman's framing model analytical methodology. First, the study finding indicates that racism is still pervasive in America. Second, the Trump administration has not done the best job of maximizing support for eradicating racism in the United States. Third, racism still exists in Hollywood, the country's main film business. Keywords: online media, the construct of media, framing, racism, Entman